Public Service of PT Angkutan Sungai Danau Dan Penyeberangan Indonesia: Case Study at the Ferry Port Bira Bulukumba Regency - Fahrul Islam, Akhmad; Hasniati, ‎; Ibrahim, Akmal (KnE Social Sciences, 2025)
This study aims to analyze the quality of public services of PT. Angkutan Sungai Danau dan Penyeberangan (PT. ASDP) Indonesia at the Bira Crossing Port of Bulukumba Regency, identify the factors that influence it, and formulate a service improvement strategy. The research method used is a qualitative approach with data collection techniques through observation, interviews, and documentation. The results showed that the quality of public services at PT ASDP Bira is not optimal, which can be seen from the unfriendliness of officers, noncompliance with standard operating procedures, and unclear ticket costs. Factors affecting public services include ineffective communication, limited human resources and facilities, and a less adaptive bureaucratic structure. Suggested strategies to improve services include strengthening human resource training, improving service support infrastructure, and implementing a stricter monitoring system. This research is expected to be a reference in improving the quality of public services in the ferry transportation sector.